Investigation of the Influence of Swallowing, Coughing and Vocalization on Heart Rate Variability with Respiratory-phase Domain Analysis - Kotani, K.; Tachibana, M.; Takamasu, K. (Methods of Information in Medicine, 2007)
Objectives: The objective of our study is to investigate extrinsic influences on heart rate variability using respiratory-phase domain analysis. Swallowing, coughing and vocalization (reading aloud and conversation) are adopted as extrinsic influences.Methods: In this study, an instantaneous R-R interval (RRI) is sampled at each π/10 rad of the respiratory phase and the data is divided into three subsets: a) respiration with event, b) one respiration after the event, and c) normal respiration. Then the mean waveforms of respiratory sinus arrhythmia (RSA) are calculated and compared.Results and Conclusions: It is found that swallowing induces tachycardia that recovers within one respiration. Coughing also induces tachycardia, but it does not recover within one respiration. Vocalization shortens the mean RRI, but the changing respiratory pattern due to vocalization has no statistically significant influence on the amplitude of RSA. Furthermore, it is found that the proposed method is effective for analyzing extrinsic influences on heart rate variability (HRV).
Keywords: Heart rate variability; respiratory phase; respiratory sinus arrhythmia